Enterprise Terraform: Optimizing Infrastructure Management with Enterprise Terraform: Enhancing Scalability, Security, and Collaboration (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Enterprise Terraform by HashiCorp is an advanced Infrastructure as Code (IaC) solution designed to manage and automate complex infrastructure environments. Building on the open-source Terraform tool, it offers enhanced features tailored for enterprise-level operations, including multi-cloud and on-premises infrastructures. Key capabilities include role-based access control (RBAC), workspaces, and policy as code through Sentinel, which collectively support secure team collaboration, governance, and compliance across infrastructure workflows. These features enable organizations to manage and provision infrastructure consistently, whether it spans on-premises systems or multiple cloud providers. Terraform Enterprise emphasizes scalability, ensuring that teams can manage large-scale infrastructure efficiently while maintaining control over resource provisioning. With tight version control system (VCS) integration, Terraform Enterprise facilitates automated deployments and consistent environment management. Remote state management and secure operations further ensure the reliability of deployments, reducing the risk of errors during infrastructure changes. By offering policy as code, team collaboration, and secure operations, Terraform Enterprise empowers organizations to streamline infrastructure provisioning, ensuring agility, consistency, and control. This research article delves into the key features of Enterprise Terraform, evaluates its implementation, and compares it with alternative IaC solutions to highlight its strengths and potential areas of improvement for enterprise use.